Brominated flame retardant BDE-99 promotes apoptosis by intrinsic mitochondrial pathway in rat liver - Elvan Bakar; Deniz Yüksel Yence; Ayşegül Çerkezkayabekir (Trakya University Journal of Natural Sciences)
This study examined in vivo effects of 2,2’,4,4’,5-pentabromodiphenyl ether (BDE-99) on the liver of Wistar Albino rats (250-300 gr) in doses of 0.05 mg/kg and 0.1 mg/kg for ten days by gavage. Our objective was to investigate the effects of BDE-99 on the apoptotic process in the liver. Previous studies have shown that BDE-99 causes accumulation and oxidative damage in various tissues, especially the liver. Although the primary mechanism of BDE-99 toxicity is known to involve oxidative stress, limited information is available on its specific impact on apoptosis. Therefore, immunoreactivity of Proliferating Cell Nuclear Antigen (PCNA), Vimentin and Topoisomeraz2A (TOP2A) and Topoisomeraz2B (TOP2B) and Terminal deoxynucleotidyl transferase dUTP Nick End Labeling (TUNEL) were determined in the liver. Superoxide dismutase (SOD), Glutathione peroxidase (GPX) and Catalase (CAT) activities were measured in the liver. qRT-PCR analyses for the p53, Bax, Bcl-2, PCNA and Vimentin genes were carried out from paraffin-embedded liver tissues. Cell membrane damage, hypertrophy, endothelial injury, mononuclear cell infiltration in the liver were determined by Hematoxylin & Eosin. Immunoreactivity of TUNEL, Vimentin, TOP2A and TOP2B increased in both doses, but immunoreactivity of PCNA significantly increased only 0.1 mg/kg BDE-99 dose (p < 0.05). SOD and GPX activities increased but CAT activity decreased significantly (p < 0.05) in the liver. Bax, Bcl-2, PCNA, Vimentin gene expressions increased in a dose-dependent manner and p53 expression increased only in 0.1 mg/kg BDE-99. In conclusion, our results point out BDE-99 inducing apoptosis of the intrinsic mitochondrial pathway in rat liver and indicate that exposure to BDE-99 is possible to be a potential risk factor for liver diseases.